The psychology of personhood philosophical, historical, social-developmental, and narrative perspectives - Martin, Jack, 1950-; Bickhard, Mark H. (Cambridge University Press, 2013)
"What is a person? Surprisingly little attention is given to this question in psychology. For much of the past century, psychology has tended to focus on the systematic study of processes rather than on the persons who enact and embody them. In contrast to the reductionist picture of much mainstream theorizing, which construes persons as their mental lives, behaviours or neurophysiological particulars, The Psychology of Personhood presents persons as irreducibly embodied and socially situated beings. Placing the study of persons at the centre of psychology, this book presents novel insights on the typical, everyday actions and experiences of persons in relation to each other and to the broader society and culture. Leading scholars from diverse academic disciplines paint an integrative portrait of the psychological person within evolutionary, historical, cultural, developmental and everyday contexts"--